(N{OSTAKOWI^(B- (NSIMFONISTs (NdRAMATURGIQ(B,(N\STETIKA(B, (NSTILX(B.(NiSSLEDOWANIEs - (Nm(B,(NsABININAs ((NmOSKWAs (NmUZYKAs, 1976)
(Nw KNIGE ISSLEDUETSQ \WOL@CIQ STILQ I DRAMATURGI^ESKIH PRINCIPOW ODNOGO IZ KRUPNEJ[IH KOMPOZITOROW(B. (NSOWREMENNOSTI(B.s
Keywords: (NmONOGRAFIQs